Antimicrobial silver-coating for locking plates shows uneventful osteotomy healing and good biocompatibility results of an experimental study in rabbits. Issue 4 (April 2020) - Arens, Daniel; Zeiter, Stephan; Nehrbass, Dirk; Ranjan, Nilabh; Paulin, Thomas; Alt, Volker
Abstract: Infections after internal fixation of fractures remain a challenge. Silver is known for its antimicrobial activity, including activity against multi-resistant strains. The aim of the current study was to analyze the biocompatibility and potential influence on the osteotomy healing process of a silver-coating technology for locking plates compared to silver-free locking plates in an established rabbit model. The implants used in this study were 7-hole titanium locking plates, and plasma electrolytic oxidation (PEO) silver-coated equivalents. A total of 24 rabbits were used in this study (12 coated, 12 non-coated). An osteotomy of the midshaft of the humerus was created and the humerus stabilized with the 7-hole locking plates with a total of 6 screws. Radiographs were taken on day 0, week 2, 4, 6, 8, and 10 for continuous radiographical evaluation. All animals were euthanized after 10 weeks and further assessment was performed using X-rays, micro-CT, non-destructive four-point bending biomechanical testing and semi-quantitative histopathological evaluation. Furthermore, silver concentration was measured in the blood, kidney, liver, spleen, brain, feces and soft tissue around the plate. Radiographs showed normal undisturbed and completed healing of the osteotomy in all animals without any differences between the two groups over the entire observation period. Micro-CT analysis revealed overall tissue volume as well as tissue density to be comparable between the two groups. Mechanical testing showed comparable stiffness with an average stiffness relative to contralateral bones of 75.7 ± 16.1% in the silver-free control group compared to 69.7 ± 18.5% (p-value: 0.46). Semi-quantitative histopathological evaluation showed no remarkable difference in the analysis of the osteotomy gap healing or in the surrounding soft tissue area. There were detectable silver concentrations in the soft tissue around the plate after 10 weeks. Silver in the blood was only found in 3 animals within the first two weeks and all animals were free of silver afterwards. There were no detectable silver concentrations in the brain, liver, spleen, axillary lymph nodes and kidney. This study shows undisturbed osteotomy healing of the presented antimicrobial silver surface coating and a good biocompatibility in this rabbit model.